IL-33/13 Axis and IL-4/31 Axis Play Distinct Roles in Inflammatory Process and Itch in Psoriasis and Atopic Dermatitis - Bodoor K; Al-Qarqaz F; Heis LA; Alfaqih MA; Oweis AO; Almomani R; Obeidat MA (Dove Medical Press, 2020)
Khaldon Bodoor,1 Firas Al-Qarqaz,2 Leen Al Heis,2 Mahmoud A Alfaqih,3 Ashraf O Oweis,4 Rowida Almomani,5 Motaz A Obeidat4 1Department of Applied Biology, Jordan University of Science and Technology, Irbid, Jordan; 2Department of Dermatology, Jordan University of Science and Technology, Irbid, Jordan; 3Department of Physiology and Biochemistry, Jordan University of Science and Technology, Irbid, Jordan; 4Department of Internal Medicine, Nephrology Division, Jordan University of Science and Technology, Irbid, Jordan; 5Department of Medical Laboratory Sciences, Jordan University of Science and Technology, Irbid, JordanCorrespondence: Khaldon BodoorDepartment of Applied Biology, Jordan University of Science and Technology, P.O.Box 3030, Irbid 22110, JordanEmail khaldon_bodoor@just.edu.joBackground: Pruritus is the most common symptom in patients with skin disease. Psoriasis and atopic dermatitis are clinically distinct inflammatory diseases. Interleukins are cytokines which play key roles in inflammatory signaling pathways.Materials and Methods: Cross-sectional study was conducted among patients with psoriasis and atopic dermatitis: 59 psoriatic patients, 56 AD patients, and 49 matched healthy controls. Interleukins 4, 13, 31, 33 serum levels were assayed by ELISA and results were compared using SPSS. Itch severity and disease severity were measured and correlation with interleukin levels was determined using SPSS.Results: The serum levels of IL-4, -13, -31, -33 were elevated in atopic dermatitis patients compared to controls. Itch and disease severity were not correlated with elevated serum levels of these interleukins. In psoriasis, the levels of IL-4 and -31 were elevated compared to controls, whereas the levels of IL-13 and -33 were lower than controls. The levels of measured interleukins in psoriasis did not correlate with itch and disease severity.Conclusion: IL-31 is the key mediator for pruritus in both AD and Ps patients. IL-4/31 axis and IL-33/13 axis play distinct roles in the pathogenesis of Atopic dermatitis and Psoriasis. Interleukin serum levels were not correlated with itch and disease severity in both conditions.Keywords: psoriasis, atopic dermatitis, pruritus, interleukins